Single-nucleus transcriptome unveils the role of ferroptosis in ischemic stroke - Cheng-Long Shi; Xiu-Li Han; Jing-Ce Chen; Qian-Fan Pan; Yong-Chao Gao; Peng-Yan Guo; Xiao-Li Min; Yong-Jun Gao (Heliyon, 2024)
Multiple cell death pathways are involved in neuronal death in ischemic stroke (IS). However, the role of different cell death pathways in different cell types has not been elucidated. By analyzing three single-nucleus RNA sequencing (snRNA-seq) data of IS, we first found that a variety of programmed cell death (PCD) -related genes were significantly changed in different cell types. Based on machine learning and virtual gene knockout, we found that ferroptosis related genes, ferritin heavy chain 1 (Fth1) and ferritin light chain (Ftl1), play a key role in IS. Ftl1 and Fth1 can promote microglia activation, as well as the production of inflammatory factors and chemokines. Cell communication analysis showed that activated microglia could enhance chemotactic peripheral leukocyte infiltration, such as macrophages and neutrophils, through Spp1-Cd44 and App-Cd74 signaling, thereby aggravating brain tissue damage. Furthermore, real‐time quantitative polymerase chain reaction (RT‐qPCR) showed that P2ry12 and Mef2c were significantly decreased in oxygen-glucose deprivation (OGD) group, while Ftl1, Fth1, Apoe, Ctsb, Cd44 and Cd74 were significantly increased in OGD group. Collectively, our findings suggested targeted therapy against microglia Ftl1 and Fth1 might improve the state of microglia, reduce the infiltration of peripheral immune cells and tissue inflammation, and then improve the ischemic brain injury in mouse.